2017
DOI: 10.3389/fphys.2017.00658
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Identified lncRNAs Associated with Renal Fibrosis in UUO Rat Model

Abstract: Renal fibrosis represents a final common outcome of many renal diseases and has attracted a great deal of attention. To better understand whether lncRNAs could be a player in this process or be a biomarker for renal fibrosis diagnosis, we compared transcriptome sequencing data on renal tissues and urine respectively between UUO (unilateral ureteral obstruction) and shamed (Sham) rat model. Numerous genes including lncRNAs with significant changes in their expression were identified. 24 lncRNAs were up-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…In addition, several TGF-β/Smad3-associated lncRNAs are found to be associated with renal fibrosis. TCONS_00088786 and TCONS_01496394 are TGF-β/Smad3-associated lncRNAs as they contain potential binding sites for Smad3 and silencing TCONS_00088786 inhibits renal interstitial fibrosis by targeting miR-132 (Sun et al, 2017;Zhou S.G. et al, 2018). lncRNA-ATB is highly upregulated in patients with acute renal allograft rejection and renal carcinoma and is able to promote EMT (Qi et al, 2017;Qiu et al, 2017;Zhou and Jiang, 2019).…”
Section: Diverse Role Of Tgf-β/smad Signaling In Regulation Of Non-comentioning
confidence: 99%
“…In addition, several TGF-β/Smad3-associated lncRNAs are found to be associated with renal fibrosis. TCONS_00088786 and TCONS_01496394 are TGF-β/Smad3-associated lncRNAs as they contain potential binding sites for Smad3 and silencing TCONS_00088786 inhibits renal interstitial fibrosis by targeting miR-132 (Sun et al, 2017;Zhou S.G. et al, 2018). lncRNA-ATB is highly upregulated in patients with acute renal allograft rejection and renal carcinoma and is able to promote EMT (Qi et al, 2017;Qiu et al, 2017;Zhou and Jiang, 2019).…”
Section: Diverse Role Of Tgf-β/smad Signaling In Regulation Of Non-comentioning
confidence: 99%
“…In recent decades, researches documented that lncRNAs were involved in variety of human diseases, such as respiratory system-related diseases, immune system-related diseases, nervous systemrelated diseases, endocrine related diseases, cardiovascular disease, urogenital system-related diseases, and variety of cancers (Wapinski and Chang, 2011;Batista and Chang, 2013;Latronico and Condorelli, 2015;Haemmig et al, 2017;Rogoyski et al, 2017). Reports demonstrated that several lncRNAs were involved in the TGF-β-induced renal fibrosis, including lncRNA H19, lncRNA ENSMUST00000147869, lincRNA-Gm4419, lncRNA Erbb4-IR, and so on (Jiang and Zhang, 2017;Sun et al, 2017). Sun et al (2018) demonstrated that Erbb4-IR promoted the renal fibrosis by inhibiting the miR-29b expression.…”
Section: Introductionmentioning
confidence: 99%
“…These lncRNAs show upregulated or downregulated expression pattern to promote or inhibit the development of diabetic complications. Onset of chronic renal failure also globally affects the expression of genes including lncRNAs, while the specific functionality of lncRNAs in this disease has rarely been studied [14]. In this study, we observed downregulated expression of lncRNA HAND2-AS1 in diabetic patients with chronic renal failure but not in diabetic patients without obvious complications.…”
Section: Discussionmentioning
confidence: 48%